CORRELATION BETWEEN WONG-BAKER FACES PAIN SCALE AND SALIVARY ALPHA-AMYLASE LEVEL IN CHILDREN AGED 6â€“11 YEARS - Anggraeni, Hastin Dian; Suharsini, Margaretha; Indiarti, Ike Siti; Yumasdhika, Faraghea (International Journal of Applied Pharmaceutics, 2018)
Objective: Several studies have tried to objectively assess pain measurements. The Wong-Baker Faces Pain Scale (WBFPS) is an instrument that is commonly used to assess pain intensity in children. This study aimed to analyze the correlation between the WBFPS and salivary alpha-amylase (SAA) level during a tooth extraction procedure with a local anesthetic injection in children aged 6â€“11 years. Methods: Twenty-five children aged 6â€“11Â years who were to undergo the extraction of a primary tooth at the Dental and Oral Educational Hospital, Faculty of Dentistry Universitas Indonesia, were enrolled in this study. From all children, saliva was collected using a disposable saliva strip shortly after local anesthetic injection, and the SAA activity was then determined using a portable Nipro Cocoro Meter device. The WBFPS was measured at the same time. The correlation between the WBFPS and the SAA level was analyzed using Spearman's correlation test. The statistically significant level was set at pâ‰¤0.05. Results: There was a significant correlation between the WBFPS and SAA level (p=0.002, r=0.581). Conclusion: Our data suggest that the SAA level might be a good index for objective pain intensity assessment.